Dynamic of Fluorescence Emissions at O2A and O2B Telluric Absorption Bands in Forested Areas with Seasonal APAR and GPP Variations - Daniel Kováč; Jan Novotný; Ladislav Šigut; John Grace; Otmar Urban (Remote Sensing, 2022)
We measured dynamics of solar-induced chlorophyll fluorescence at telluric oxygen absorption bands O2A and O2B in evergreen spruce and deciduous beech forests. Seasonal variations in fluorescence emissions were compared with NDVI. Daily changes in fluorescence emissions were compared with canopy shadow fraction (αS) dynamics, which showed impact of branch and leaf positions on detected fluorescence signals based on comparison with canopy height model. Absorbed photosynthetically active radiation (APAR) was recognized as a large determinant of fluorescence changes within the O2A band (SIFA), with R2 > 0.68. Fluorescence within the O2B band was more directly linked to NDVI. Although, the seasonal dynamics of fluorescence within the O2B band (SIFB) were similar to SIFA in the spruce forest. In the beech forest, SIFB showed different seasonal dynamics as compared with SIFA. SIFA in the spruce forest showed a relationship to gross primary productivity (GPP), with R2 = 0.48, and a relationship of R2 = 0.37 was estimated for the SIFA-GPP connection in the beech forest. SIFB was better linked to seasonal GPP in the beech forest, but with a negative slope in the relationship with R2 = 0.61. We have shown that measurements of passive fluorescence signals at telluric oxygen absorption bands can contribute to understanding to photosynthesis processes in forest canopies.